2014
DOI: 10.1002/cb.1484
|View full text |Cite
|
Sign up to set email alerts
|

Household pre‐purchase practices and online grocery shopping

Abstract: This paper explores household pre-purchase practices and their mediation by information and communications technologies (ICTs), specifically online grocery shopping. Drawing on practice theory, the impacts of ICTs on household grocery shopping behavior are conceptualized, and the concept of "front-loading" is introduced. Emerging themes generated from 31 semi-structured interviews conducted via Skype with Turkish consumers focusing on their experiences of online grocery practices are presented. To this end, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…35 The studies covered a range of issues related to online retail of foods, from retailer perspectives [36][37][38][39] to consumer attitudes toward buying groceries online. 32,[40][41][42][43][44][45] Online food delivery services (of fast food and other ready meals) [46][47][48] also emerged as part of the typology of food vendors in the digital food environment. This includes restaurants and other vendors of ready meals that have their own smartphone applications and websites, as well as third party food delivery aggregators (such as Swiggy, Zomato, and Uber Eats).…”
Section: External Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The studies covered a range of issues related to online retail of foods, from retailer perspectives [36][37][38][39] to consumer attitudes toward buying groceries online. 32,[40][41][42][43][44][45] Online food delivery services (of fast food and other ready meals) [46][47][48] also emerged as part of the typology of food vendors in the digital food environment. This includes restaurants and other vendors of ready meals that have their own smartphone applications and websites, as well as third party food delivery aggregators (such as Swiggy, Zomato, and Uber Eats).…”
Section: External Domainmentioning
confidence: 99%
“…While no studies investigated convenience in depth, the existing studies indicated that convenience in the digital food environment can be influenced by food delivery apps that reduce or eliminate time preparing and cooking food, 100,153 by the improved meal planning afforded by food recipe websites and apps, 154 and online grocery shopping. 43,44,77,112,126,145,155,156…”
Section: Affordabilitymentioning
confidence: 99%
“…Numerous studies were carried out to understand the socio-demographic profile of consumers who have adopted online grocery services (Raijas, 2002; Hansen, 2005; Clark and Wright, 2007; Ramachandran et al , 2011). The pre-purchase behavior of households was one factor that determined the use of online grocery shopping (De Kervenoael et al , 2014). Recently, Van Droogenbroeck and Van Hove (2017) studied the effect of both demographic and household characteristics on online grocery adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The abstract screen yielded nine papers for inclusion in the review. Of the seven excluded at the abstract screen, four were excluded due to not being based in the USA or Europe (37)(38)(39)(40) and three were excluded due to not being about the topic areas of interest (41)(42)(43) .…”
Section: Framework Stage 1: Identify the Research Questionmentioning
confidence: 99%